Right to Health under the Colombian Neoliberal Model - Camargo-Lombana, Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The article seeks to characterize the infringement of the right to health and the current situation of health in Colombia, considering that this right is framed in the neoliberal economic model. It is understood that health is a comprehensive welfare state, according social medicine and not merely the absence of disease.We propose the State as responsible for the guarantee of rights of the individual, in this case,a psychoactive substance consumer, which responds to a socio-historical concept, that is constructed in social contexts such as education, work and nutrition and that requires land ownership to be recognized with equal rights.